Diagnosis of seeds supply of leafy vegetables in Yaoundé, Cameroon - Pousseu, L; Pegalepo, E; Kouamé, C; Bell, JM; Kamga, RT (African journal of food, agriculture, nutrition, and development : AJFAND, 2014)
The traditional leafy vegetables play a major role in the Cameroonian diet. In the metropolitan zone of Yaoundé, these vegetables are produced year round in family and commercial exploitations. The quality of the seeds, their mode of production and their system of distribution are little known. With the aim to better understand the seed system of traditional vegetables, a study on the supply, the production and the quality of these seeds was carried out. The data were collected using questionnaires on a sample of 133 traditional leafy vegetable producers of the urban and peri-urban zone of Yaoundé. The data were analyzed using SNAP 9 software. The study showed that the most produced species are amaranth (Amaranthus cruentus), nightshade (Solanum scabrum) and jute mallow (Corchorus olitorius). The market-gardeners are influenced in their choice of vegetable to cultivate by the preference of the customers (85.7% of the respondents) and the productivity of the cultivars (66.2% of the respondents). More than 40% of the respondents buy seeds in the markets while 7.5% buy seed from other producers and 10.5% in the agricultural inputs stores. About half (47.4%) of the respondents produce seeds by leaving plants in the field after the first or the second harvest while 36.8% of the market-gardeners select the most vigorous plants for seed production. On average, 58.7% of respondents preserve the seeds in hermetically closed bottles and plastic bag. Storage on field is practiced by a significant part of market-gardeners (41.4%). A total of 79.7% of the producers reported constraints with the produced seeds. Poor seed germination (81.1% of respondents) and the non uniformity of the seed (48.1% of the producers) were reported as the major constraints. The principal source of seed supply in the metropolitan zone of Yaoundé is the self production with rudimentary production and storage techniques subject to many qualitative constraints.